Študij detajliranja na Fakulteti za arhitekturo v Ljubljani - Kalčič, Igor (AR. Arhitektura, raziskave, 2004)
The detail is the smallest but probably most important element of architectural language. Detailing mainly implies composition of various independent materials into new complex joints: metal and glass, wood and concrete, wood and glass, stone and concrete, metal and wood etc., or even more complicated and complex: concrete, metal and glass, concrete, metal and wood, metal, wood and glass etc. When assembling different materials into joints, the applied "rules of the game" are different than in simpler combinations of equal materials. The course introduces some new parameters to design of details that are closer to engineering and, as a rule, economic factors (rationality), which are often decisive in decision making. In such assembly, the rules of the game precisely follow technology and respect chemical and physical solutions, but also other important engineering aspects. In the last phase of the process of conceptualisation and design of details, the aesthetic component is introduced, which is extremely important for architects and ensures that the product will be likable and offer its users aesthetic satisfaction. In the course work and under tutor control, students have to work in a multidisciplinary fashion, consciously and aligned to all principles of contemporary European engineering. They have to produce a detailed project for a selected building, present it in a modern manner and use one of the generally acclaimed computer programmes that are used in engineering architecture.
Keywords: Fakulteta za arhitekturo; Ljubljana; študij; arhitekturna kompozicija; detajli; tehnika; estetika; aesthetics